Evaluation of Technical Assistance on Bank Supervision by Long-Term Experts in Asia. (Policy Papers; Policy Paper ;, 2009)
Technical Assistance Delivery by Long-Term Experts are an increasingly important vehicle for delivering TA in all financial sector areas. In recent years, the amount of MCM TA provided through LTEs has been about 28 staff years annually, or 36 percent of MCM's total TA field delivery (including RTACs). This share has recently risen as a result of the steady increase in external financing and the cutback in MCM's own resources for capacity building in the context of the recent downsizing. Indeed, the share of LTEs (who are mostly externally financed) in total planned MCM TA jumped to 41 percent in fiscal year 2009 (May-April). As these factors are expected to persist, the importance of LTEs as a means of delivering TA will likely increase further.